2008
DOI: 10.1016/j.jpeds.2008.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Treatment for Growth Failure in Pediatric Patients with Crohn's Disease

Abstract: Objective-We determined the impact of human growth hormone (GH) injections on growth velocity in growth impaired children with Crohn's Disease (CD). Study design-Ten children and adolescents (12.6±4.5 years; 6 male) with CD and poor height growth were treated with open label recombinant GH 0.043 mg/kg/day SQ for one year. Patients were retrospectively matched with untreated patients (3 comparisons per case) by race, age, sex, and baseline height. Primary endpoint was height velocity; secondary endpoints were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
5
19
1
Order By: Relevance
“…Although a preliminary study suggested a beneficial effect of recombinant human GH (rhGH) treatment on disease activity in 37 adults with CD [108], these results were not confirmed afterwards [109]. As rhGH treatment appears to exert no effect on disease activity, it has no place in the first-line treatment strategies of IBD patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a preliminary study suggested a beneficial effect of recombinant human GH (rhGH) treatment on disease activity in 37 adults with CD [108], these results were not confirmed afterwards [109]. As rhGH treatment appears to exert no effect on disease activity, it has no place in the first-line treatment strategies of IBD patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, this trial included a very small number of subjects and the results are controversial. While in some studies [109,111,112] height velocity, bone mineral density and body composition were improved, no significant improvement of nutritional status could be shown in others [113,114]. Mauras et al [111] described favorable changes in body composition and linear growth in 10 glucocorticoid-dependent IBD children treated with high-dose rhGH for 4 months, suggesting that rhGH therapy could counteract the inhibitory effect of glucocorticoids.…”
Section: Resultsmentioning
confidence: 99%
“…In another study of 10 children with CD treated with 12 months of rhGH (0.043 mg/kg/day), DXA LS BMD SDS adjusted for age increased by +0.31 SD [3]. However, the need to adjust DXA BMD and body composition data for size is now well recognized and addressed in our current study.…”
Section: Discussionmentioning
confidence: 67%
“…In accordance with an anabolic effect of GH, previous studies of recombinant human growth hormone (rhGH) therapy in children with chronic inflammation such as juvenile arthritis showed that, in addition to an increase in height, significant improvements in bone and muscle area were observed [2]. The effects of rhGH on the muscle-bone unit in CD has rarely been studied [3, 4]. A recent study in mice with colitis showed that deletion of the suppressor of cytokine signalling 2, a negative regulator of GH signalling, may be protective against the bone loss associated with inflammation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have tried to answer this question. A small case control study has shown short-term (up to 1 year) therapeutic efficacy of rhGH in improving linear growth in children with CD standard maintenance therapy [135]. In contrast, a small randomized controlled trial by Calenda et al [136] failed to reveal any difference in growth parameters between children treated or untreated with rhGH.…”
Section: Hormonal Therapymentioning
confidence: 98%